2020
DOI: 10.1186/s13046-020-01735-3
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the KDM5A/miRNA-495/YTHDF2/m6A-MOB3B axis facilitates prostate cancer progression

Abstract: Background Accumulating evidence supports that lysine-specific demethylase 5 (KDM5) family members act as oncogenic drivers. This study was performed to elucidate the potential effects of KDM5A on prostate cancer (PCa) progression via the miR-495/YTHDF2/m6A-MOB3B axis. Methods The expression of KDM5A, miR-495, YTHDF2 and MOB3B was validated in human PCa tissues and cell lines. Ectopic expression and knockdown experiments were developed in PCa cells to evaluate their effects on PCa cell proliferation, migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 22 publications
3
61
0
Order By: Relevance
“…Previous studies revealed that m6A mark acted as a key post-transcriptional modification that promoted the initiation of miRNA biogenesis [52] . Moreover, H3K4me3 demethylase, bound to the miRNA promoter, which led to inhibition of its transcription and expression [53] . SnoRNAs, involving in ribosome biogenesis and RNA modification, acted as endogenous sponges that regulate miRNA expression [54] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that m6A mark acted as a key post-transcriptional modification that promoted the initiation of miRNA biogenesis [52] . Moreover, H3K4me3 demethylase, bound to the miRNA promoter, which led to inhibition of its transcription and expression [53] . SnoRNAs, involving in ribosome biogenesis and RNA modification, acted as endogenous sponges that regulate miRNA expression [54] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, KDM5A mediates reduction in methylated H3K4 and thus decreases the levels of two tumor suppression and differentiation genes KLF4 and E-cadherin , which lead to the malignancy of PCa [ 97 ]. KDM5A is also capable of promoting PCa progression via the KDM5A/miRNA-495/YTHDF2/m6A-MOB3B axis [ 98 ].…”
Section: Kdm5a In Human Cancermentioning
confidence: 99%
“…miR-145 was implicated in the regulation of m6A levels of HCC by targeting YTHDF2 [57]. Furthermore, decreased expression of miR-495 and miR-493-3p leaded to upregulated YTHDF2 and enhanced proliferation and invasion in prostate cancer [58,59]. Therefore, we nally performed differential microRNA expression analysis and observed that YTHDF2 was the target of miR-205, which was decreased in MM and negatively correlated with YTHDF2.…”
Section: Discussionmentioning
confidence: 97%